Nanostructures in Energy Generation, Transmission and Storage - Fedorenko, Yanina (IntechOpen, 2019)
Today, clean natural resources, global warming, energy production, transmission and storage are the most widely discussed topics and main directions of scientific research. This book presents a collection of research contributions addressing recent achievements in nanoscience to mitigate societal challenges of environmental pollution and energy shortage. The environmental control, forensics and virtually any industry rely on the newest advances in nanoscience and sustainable technologies. Nanostructured materials explored in ultrasensitive sensors aid in global environmental monitoring, medical diagnostics and energy conversion applications. Global energy resources - solar energy, hydrogen generation and the oceans - are being effectively explored owing to the discovery of new materials for photo- and photo-electrochemical energy conversion, hydrogen generation and storage, water purification and desalination, environmental control and information processing.